SIFAT-SIFAT SEMIGRUP TRIPEL DAN SEMIGRUP TRIPEL DE MORGAN ATAS FUNGSI TERNER - , ZAHIROTUL KAMILIYAH, Dr.rer.nat. Yeni Susanti, S.Si., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In this final project, we discuss some properties of a particular triple semigroup of ternary functions under three binarys operations defined on it. We discuss some properties, namely: zero left elements, the properties of the three operations, the necessary and sufficients conditions such that two triple semigroups are isomorphic, the ideals, and all congruences. We also discuss the characters of a particular type of ternary function, ie. de Morgan triple semigroup of ternary functions, the sufficient and necessary conditions that any two de Morgan triple semigroups with the same operations are isomorphic.